Doctor who? The effect of physician-patient match on the SES-health gradient - Ida Lykke Kristiansen; Yanying Sheng (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
We investigate whether primary care physician and patient concordance in terms of socio-economic status (SES) reduces the SES inequality in health. We measure physicians' SES by their childhood SES and find that SES concordance decreases low-SES patients' mortality, while high-SES patients' mortality does not depend on their physicians' background. Together, they translate to a 24% reduction in the SES-mortality gradient. SES concordance changes the health behavior of the patient and increases treatment of chronic conditions: low-SES patients with lowSES physicians receive more care at the intensive margin, have a higher detection of chronic conditions, and have higher adherence to treatment.
Keywords: I12; I14; J62; 330; Health inequality; physician practice style; intergenerational transmission; family background; socio-economic status; health behaviors